Droplet and bubble formation of combined oil and gas releases in subsea blowouts. Issue 1 (15th July 2017) - Zhao, Lin; Boufadel, Michel C.; King, Thomas; Robinson, Brian; Gao, Feng; Socolofsky, Scott A.; Lee, Kenneth
Abstract: Underwater blowouts from gas and oil operations often involve the simultaneous release of oil and gas. Presence of gas bubbles in jets/plumes could greatly influence oil droplet formation. With the aim of understanding and quantifying the droplet formation from Deepwater Horizon blowout (DWH) we developed a new formulation for gas-oil interaction with jets/plumes. We used the jet-droplet formation model VDROP-J with the new module and the updated model was validated against laboratory and field experimental data. Application to DWH revealed that, in the absence of dispersant, gas input resulted in a reduction of d50 by up to 1.5 mm, and maximum impact occurred at intermediate gas fractions (30–50%). In the presence of dispersant, reduction in d50 due to bubbles was small because of the promoted small sizes of both bubbles and droplets by surfactants. The new development could largely enhance the prediction and response to oil and gas blowouts. Highlight: New formulation of gas-oil interaction for simultaneous release of oil and gas in subsea blowouts Good agreement between modeling results and laboratory and field experimental data Reduced oil droplet size due to the presence of bubbles during the Deepwater Horizon blowouts Less effects of droplet reduction due to bubbles in the presence of dispersant from DWH blowouts